Autoimmune thyroid disease in diabetic children and adolescents: a single center study from south Punjab - Waqas Imran Khan; Erum Afzal; Sajjad Hussain (Journal of the Pakistan Medical Association, 2021)
Objective: To evaluate the prevalence of autoimmune thyroid disease (AITD) in diabetic children in south Punjab. Methods: This was an observational cross sectional study from Jan 2019 to Dec 2019 in the outpatient diabetic clinic of the department of pediatric endocrinology at Children Hospital and The Institute of Child Health Multan. A total of 161 consecutive patients of both genders with TIDM were enrolled in this study after taking informed consent. Blood samples for Thyroid functions testes including thyroid stimulating hormone (TSH), free thyroxin (fT4), Thyroid peroxidase antibody (TPO-Ab), thyroglobulin antibody (TG-Ab) and glycosylated hemoglobin (HbA1C) level were sent. Results: Among diabetic children males were 83 (51.6%). Age range was 2-15 years. Mean age and standard deviation was 9.7± 4.3. TPO-Ab was positive in 34 patients (21.1%) and TG-Ab in 27 patients (16.7%), whereas both antibodies were positive in 17 patients (10.5%). Six patients (3.7%) had evidence of subclinical hypothyroidism, 8 patients (4.9%) had overt hypothyroidism and 1 patient (0.62%) had hyperthyroidism Conclusion: The prevalence of AITD among children and adolescents with type 1 diabetes mellitus was 21.1% in our study. Hypothyroidism was more prevalent in these children compared to hyperthyroidism. All diabetic children should be screened for AITD. Thyroid functions should be checked where TPO antibody is positive. Keywords: Autoimmune thyroid disease, anti thyroid peroxidase antibody, anti thyroglobulin Continuous...